Effect of Using Different Vehicles on the Physicochemical, Antimicrobial, and Biological Properties of White Mineral Trioxide Aggregate - Cavenago, Bruno Cavalini; del Carpio-Perochena, Aldo Enrique; Ordinola-Zapata, Ronald; Estrela, Carlos; Garlet, Gustavo Pompermaier; Tanomaru-Filho, Mario [UNESP]; Weckwerth, Paulo Henrique; Andrade, Flaviana Bombarda de; Hungaro Duarte, Marco Antonio (Elsevier B.V., 2017)
Introduction: This study evaluated the physicochemical, antimicrobial, and biological properties of white mineral trioxide aggregate (MTA) mixed with aqueous and propylene glycol extracts of Arctium lappa L. and Casearia sylvestris Sw. Methods: The setting time test was performed according to American Society for Testing and Materials 266/2008 and flowability by American National Standards Institute/American Dental Association 57/2012 standard specifications. The following parameters were assessed: volumetric change by micro computed tomography; pH level and calcium ion release measured after 3 hours and 1, 3, 7, and 15 days; antimicrobial effect by the dentin decontamination method with intratubular Enterococcus faecalis viability, verified by using confocal laser scanning microscopy; and biocompatibility by histologic-morphometric analyses of inflammatory infiltrate at subcutaneous implant sites after 15, 30, and 60 days. In addition, rat alveolar tissues with implants were processed to measure tumor necrosis factor-alpha and interleukin-10 cytokines by enzyme-linked immunosorbent assay. Results: The plant extracts associated with MTA significantly increased the final setting time; however, they did not influence volumetric change (P > .05) and maintained medium alkalinity and calcium ion release. Propylene glycol extracts showed higher flowability. Casearia sylvestris increased the cementing effect against E. faecalis after 24-hour and 168-hour periods. Histologic evaluation of inflammatory infiltrate showed no significant differences between plant extracts groups and the distilled water group for all periods. Tumor necrosis factor-alpha and interleukin-10 expression was similar among groups (P > .05). Conclusions: Casearia sylvestris extracts increased the antimicrobial effect of MTA and did not influence biocompatibility but changed some physicochemical properties.
Keywords: Biocompatibility; Enterococcus faecalis; material testing; phytotherapy